Improvement of Methods of Standardisation of Medicinal Products Made from Veratrum Lobelianum Rhizomes with Roots - N. P. Antonova; I. M. Morgunov; S. S. Prokhvatilova; E. P. Shefer; O. V. Evdokimova; A. V. Beketova; M. N. Lyakina (Регуляторные исследования и экспертиза лекарственных средств, 2021)
Abstract. Identification of hellebore (Veratrum Lobelianum Bernh.) herbal substance, as well as hellebore-based herbal preparation and herbal medicinal product by the same group of biologically active substances using the same test method is in line with the so-called “consistent standardisation” principle.The aim of the study was to develop a harmonised approach to identification of steroidal alkaloids in hellebore products (hellebore water, hellebore tincture) and hellebore herbal substance (hellebore rhizomes with roots).Materials and methods: samples of hellebore water, hellebore tincture, and hellebore rhizomes with roots were analysed by high-performance thin-layer chromatography (HPTLC) using an HPTLC plate.Results: the authors developed a harmonised identification procedure for products made from hellebore rhizomes with roots (herbal substance, herbal preparation, and herbal medicinal product) based on HPTLC detection of steroidal alkaloids. The results of the study will be used to prepare amendments to the Identification part of monograph FS.2.5.0104.18 “Hellebore rhizomes with roots”. The developed test procedure is proposed for inclusion into draft monographs “Hellebore rhizomes with roots, tincture” and “Hellebore rhizomes with roots, tincture, solution for external use”.Conclusions: the developed test procedure can be used as an identification test for a range of products from the hellebore herbal substance to hellebore-based herbal medicinal products, which is based on the detection of the same group of biologically active substances.